Comparison of Individualized Rescue Luteal Phase Support Strategies with Vaginal and Combined Vaginal & Subcutaneous Progesterone Administration in Artificial Frozen-Thawed Blastocyst Embryo Transfer Cycles Based on Serum Progesterone levels - Arik Alpcetin, Secil Irem; Ince, Onur; Akcay, Bengisu; Cevher Akdulum, Munire Funda; Demirdag, Erhan; Erdem, Ahmet; Erdem, Mehmet (Frontiers in Endocrinology, 2025)
ObjectivesHormone replacement therapy (HRT) frozen embryo transfer (FET) cycles are common in assisted reproductive techniques. As the corpus luteum is absent in these cycles, luteal phase support is provided by administering progesterone (P4) through transvaginal, parenteral, or oral routes. Low serum levels of P4 (below 9-10 ng/mL) on the day before embryo transfer (ET) have been associated with unfavorable cycle outcomes. The aim of this study is to investigate whether individualizing luteal support through rescue protocols in patients with low serum P4 levels improves pregnancy outcomes in HRT-FET cycles.Material and methodThis retrospective, single-center cohort analysis includes 1257 cycles involving 942 patients undergoing HRT-FET. Starting in 2019, we have assessed P4 levels before ET day and adjusted MVP doses when P4 levels were <10 ng/mL. In 2021, subcutaneous (SC) P4 was routinely added alongside MVP, with SC doses increased if P4 levels were <10 ng/mL. In this study, Groups 1 and 2 received MVP for luteal support, while Groups 3 and 4 received additional SC progesterone. For patients with P levels below the cut-off level (10 ng/mL) in Groups 2 and 4, the P dose was doubled through a rescue protocol.ResultsIn the MVP and MVP plus SC groups, 15.8% and 8.9% of the cycles had P4 levels <10 ng/mL, respectively. Ongoing pregnancy rates (OPR) and clinical pregnancy rates (CPR) did not differ between study groups. Regression analysis with a mixed model revealed that age, endometrial thickness, and estradiol levels were confounding factors as well as independent predictors of ongoing pregnancy rates (p<0.05). Pairwise regression analysis revealed no significant differences in pregnancy rates between the groups (p>0.05).ConclusionIndividualizing luteal phase support based on serum P4 levels on the day of ET in FET cycles with HRT may enhance pregnancy outcomes by either doubling the vaginal dose or increasing the SC dose during MVP plus SC administration. The implemented rescue protocol allowed patients with low progesterone levels to achieve pregnancy outcomes similar to those with higher progesterone levels.